EVALUATION OF THE REDUCTION IN UNCERTAINTY OBTAINED BY CONDITIONING A 3D STOCHASTIC CHANNEL TO MULTIWELL PRESSURE DATA - Zhang F.; Reynolds A.C.; Oliver D.S. (My University, 2002)
A stochastic channel embedded in a background facies is conditioned to data observed at wells. The background facies is a fixed rectangular box. The model parameters consist of geometric parameters that describe the shape, size, and location of the channel, and permeability and porosity in the channel and nonchannel facies. We extend methodology previously developed to condition a stochastic channel to well-test pressure data, and well observations of the channel thickness and the depth of the top of the channel. The main objective of this work is to characterize the reduction in uncertainty in channel model parameters and predicted reservoir performance that can be achieved by conditioning to well-test pressure data at one or more wells. Multiple conditional realizations of the geometric parameters and rock properties are generated to evaluate the uncertainty in model parameters. The ensemble of predictions of reservoir performance generated from the suite of realizations provides a Monte Carlo estimate of the uncertainty in future performance predictions. In addition, we provide some insight on how prior variances, data measurement errors, and sensitivity coefficients interact to determine the reduction in model parameters obtained by conditioning to pressure data and examine the value of active and observation well data in resolving model parameters.
Keywords: CONDITIONAL SIMULATION; STOCHASTIC CHANNEL; UNCERTAINTY EVALUATION; PRESSURE TRANSIENT ANALYSIS